2021
DOI: 10.1111/dth.15088
|View full text |Cite
|
Sign up to set email alerts
|

Switching infliximab in psoriatic patients during COVID ‐19 pandemics: A real‐life retrospective study comparing intra‐versus interclass switching strategies

Abstract: During this pandemic, dermatological infusion centers were partially unavailable, suspended or even reconverted to guest COVID‐19 patients, consequently infliximab (IFX) infusions became challenging for their both logistic arrangement and also for patients' COVID‐19 phobia. This 48 weeks follow‐up retrospective observational study included 37 PsO patients that underwent IFX SB2 during pandemic in two primary dermatological referral centers. In 23 (62.1%) we had to switch from IFX to other biologics, not motiva… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…These options enrich the dermatological armamentarium to treat plaque psoriasis, but actually, beside the PASI75 failure at week 16 and drug-related major adverse events, no clear switching criteria are validated, making study comparison very challenging, since switching criteria are usually not even reported. In Italy, that has a universalistic healthcare system, we recently experienced three type of biologic switching: clinically driven (loss of function of the previous drug), pharmaco-economic driven (only from originator to biosimilar or from biosimilar to biosimilar) and COVID-19 pandemic driven (to drugs that deserves less administration per year to avoid hospitals) [21]. Furthermore, comparing universalistic (i.e., Italy) and non-universalistic healthcare systems (i.e., US), two main differences in switching appear: in non-universalistic systems the switching may be performed also in case of insurance changes and the use of biosimilar is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…These options enrich the dermatological armamentarium to treat plaque psoriasis, but actually, beside the PASI75 failure at week 16 and drug-related major adverse events, no clear switching criteria are validated, making study comparison very challenging, since switching criteria are usually not even reported. In Italy, that has a universalistic healthcare system, we recently experienced three type of biologic switching: clinically driven (loss of function of the previous drug), pharmaco-economic driven (only from originator to biosimilar or from biosimilar to biosimilar) and COVID-19 pandemic driven (to drugs that deserves less administration per year to avoid hospitals) [21]. Furthermore, comparing universalistic (i.e., Italy) and non-universalistic healthcare systems (i.e., US), two main differences in switching appear: in non-universalistic systems the switching may be performed also in case of insurance changes and the use of biosimilar is extremely rare.…”
Section: Discussionmentioning
confidence: 99%
“…Due to the chronic nature of psoriasis [1][2][3], the affected patients may experience several comorbidities (i.e., respiratory [4][5][6][7][8], cardiovascular [9][10][11][12][13] or gastrointestinal ones [14][15][16][17]) and therapy failures [18][19][20][21][22][23][24][25]. Thus, therapeutic strategies play a pivotal in limiting the psoriasis detrimental progression and the quality of life worsening.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…The findings of one study found no benefit for using infliximab in COVID‐19 patients in terms of the length of hospital stay. 74 According to the findings of meta‐analysis, patients taking infliximab showed earlier hospital discharge compared with the control group. Nonetheless, infliximab showed no benefit in terms of mortality rate.…”
Section: Discussionmentioning
confidence: 99%